Analysis of performance optimization methods for 3D games in the Unity environment - Potręć, Maciej; Badurowicz, Marcin (Journal of Computer Sciences Institute, 2025)
The paper analyzes methods for optimizing performance in 3D games created in Unity. Based on the literature, the following techniques are discussed: GPU Instancing, Static Batching, Occlusion Culling, Level of Detail (LOD), Unity Jobs, Object Pooling, and the tick system. In four test scenarios, metrics (FPS, RAM, batch count) were collected using Unity Profiler. The results showed that GPU Instancing and Static Batching increase FPS (10,9 % and 20,4 %) and reduce memory usage, while LOD increases FPS by over 380 % with a minimal increase in RAM. Occlusion Culling is only effective with large objects. Unity Jobs, Object Pooling, and ticks improve performance by 14-27 %. The choice of methods should depend on the nature of the scene. Further research on other platforms is recommended.